BS15 Multiplexed measurement of protein biomarkers of cardiovascular disease in blood. (May 2019) - Tonry, Claire; Glezeva, Nadezhda; Rooney, Cathy; Hernandez, Belinda; Morrissey, Brian; Ledwidge, Mark; McDonald, Ken; Pennington, Stephen; Baugh, John; Watson, Chris
Abstract : Brief introduction: Almost half of all deaths in Europe are attributable to by Cardiovascular Disease (CVD). There is a critical unmet need for better biomarkers so that CVD can be diagnosed at an earlier stage and with greater accuracy. Mass spectrometry-based multiple reaction monitoring (MRM) allows for rapid, targeted measurement of multiple protein biomarkers via detection of 'proteotypic' peptide fragments. Such assays can be developed in blood samples, which is desirable for minimally-invasive, routine monitoring of cardiovascular health. The purpose of this study was to design a robust MRM-based assay for the simultaneous detection and measurement of a panel of 36 proteins, including 19 known and 17 novel protein biomarkers of CVD, in blood. The overall aim was to evaluate the potential clinical utility of this biomarker panel for prediction of heart failure in a cohort of 500 patients. Explanation of basic methods: Proteotypic peptides for each of the 36 candidate biomarker proteins were identified using Skyline and Spectrum Mill PeptideSelector software. MRM assays were developed using nanoflow reverse phase C18 chromatographic ChipCube based separation, coupled to a 6460 triple quadrupole mass spectrometer. Patient samples and synthetic peptides were used to obtain reference MS/MS spectra for building high quality MRM assays. For initial verification of the candidate protein biomarker panel, the MRM assay was applied, in a sample blinded manner, to a cohort of 500 serum samples from patients with heart failure and age-matched non-heart failure controls with CVD risk-factors. Results: MRM assays were established for 35 peptides, corresponding to 9 of the known candidate biomarker proteins and all 16 of the novel biomarkers (Table 1 ). Individually, a number of the biomarker proteins show differential expression between heart failure with preserved and reduced ejection fraction (Table 2 ). Combined measurement of all biomarker proteins was found to have greater predictive capacity for heart failure than the current gold standard of B-type natriuretic peptide (BNP) alone. A statistical mode found that the biomarker panel, combined with BNP was capable of correctly predicting heart failure in blinded patient samples with accuracy of 82.19% AUC of 0.89 (Figure 1 ). Conclusions/Implications: Through this study, assays have been developed for robust, multiplexed measurement of 26 CVD biomarker proteins in patient serum samples. Here it was observed that measurement of the full panel of CVD protein biomarkers offers more accurate prediction of heart failure than measurement of BNP alone. This panel will need to be further validated in independent patient cohorts. Conflict of interest: None